An Evaluation of microbial leakage in three different implant abutment connections using a quantitative analysis of presence of staphylococci bacteria an in vitro study - Desai, Pranav (International Journal of Health, 2024)
Dental implants have become a mainstay in providing fixed/semi fixed restorations successfully in the past few decades. One crucial component of dental implant which immensely contributes to the osseointegration and long term success of the restoration is the implant abutment connection (IAC). The IAC houses a microgap that can cause leakage of microorganisms which would then act as a bacterial reservoir. We performed a laboratory study to evaluate the microbial leakage occurring within the IAC between three different popularly used implants. The samples were divided into three groups based on their IAC – Conelog connection (Biohorizon), Conexa connection (B and B) and Internal Octagon (Osstem). The implant analog – abutment assemblies to be studied were immersed in a peptone broth containing Staphylococci bacteria. After an incubation period of 14 days, these assemblies were disassembled and a swab was taken from the inner surface of the implant analog and abutment. This swab was plated and after 48 hours, colonies of Staphylococci were counted. From the study, it was clear that microbial leakage had taken place in all the groups. This will help us to guide the decision of which is the most suitable implant to be used to provide a successful long term prosthesis to the patient.